Bridging the Gaps in Employee Volunteering: Why the Third Sector Doesn't Always Win. (February 2018) - Cook, Joanne; Burchell, Jon
Employee Volunteering (EV) schemes represent a cornerstone of many company Corporate Social Responsibility (CSR) strategies, being identified as a classic "win-win" situation in which businesses contribute significant resources into local communities while gaining a more skilled and engaged workforce and increased reputational benefits. This article questions the "win-win" scenario of EV arguing that existing research has focused predominantly upon the business–employee dimension while largely ignoring the role of third sector organizations engaging in these relationships. By focusing more directly on third sector experiences, the article identifies four "gaps" which place considerable constraints on the reach and impact of EV. It demonstrates the importance of not simply presuming a "win" for the third sector and the added value that can be gained from redirecting EV research toward the "business/nonprofit interface."